A Novel, Biodegradable, Thermoresponsive Hydrogel Attenuates Ventricular Remodeling and Improves Cardiac Function Following Myocardial Infarction - a review - Yi, Xin; Li, Xiaoyan; Ren, Shan; He, Yiyu; Wan, Weiguo; Wen, Ying; Jiang, Xuejun (Current Pharmaceutical Design, 2014)
Myocardial infarction (MI) and the subsequent heart failure remain among of the leading causes of morbidity and mortality in world wide. A number of studies have demonstrated that intramyocardial biomaterials injections improve cardiac function after implantation because of their angiogenic potential. Thermoresponsive hydrogels, one member of the hydrogels family, are a kind of biomaterial whose structure is similar to that of extracellular matrix. These hydrogels have been interesting for biomedical uses as they can swell in situ under physiological conditions and provide the advantage of convenient administration. The hydrogel that our team is interested in is a novel biodegradable injectable thermoresponsive hydrogel-the copolymer dextran-poly (ε-caprolactone) -2-hydroxylethyl methacrylatepoly (N-isopropylacrylaminde) (Dex-PCL-HEMA/PNIPAAm). Thus, this review will focus on requirements and challenges of injectable synthetic material, and possible mechanism of thermoresponsive hydrogel in treating MI. The main emphases are on the work done and future interesting studies in our laboratory.
Keywords: ventricular remodeling